Nutrient removal from hydroponic effluent by Nordic microalgae: From screening to a greenhouse photobioreactor operation - Salazar João; Valev Dimitar; Näkkilä Juha; Tyystjärvi Esa; Sirin Sema; Allahverdiyeva Yagut (ELSEVIER, 2022)
To guarantee year-round horticultural production, Nordic countries rely on greenhouses to cope with the harsh winter conditions. Despite substantial progress in greenhouse operation, greenhouse effluents are still overloaded with nutrients and are known to be a source of eutrophication that decreases the quality of natural waters worldwide. Here we investigate the possibility of recirculating hydroponic effluents from a commercial cucumber greenhouse to cultivate photoautotrophic microalgal biomass. A stepwise methodology was applied to scale-up procedures from laboratory to a pilot scale photobioreactor (PBR) which was operated inside a greenhouse. The screening results identified that 12 (of 13) strains were capable of proliferating in the hydroponic effluent without any adjustment or dilution. A Nordic microalga from the Scenedesmaceae family was selected for a PBR operation which lasted 36 days. This continuous cultivation was undertaken under four different test conditions and removal efficiencies between 18 and 35% for N-NO3- and 40?98% for P-PO43- were achieved. Over 1000 L of hydroponic effluent was recirculated, with a steady N-NO3- uptake of 86?92 mg g-1 and a P-PO43- uptake of 11?21 mg g-1 biomass. These results demonstrated that a hydroponic effluent N:P of 15?26 and pH of 7.5 were the most appropriate conditions for nutrient uptake, although increasing the pH to 9 may promote P-PO43- uptake. Overall, this work indicates the feasibility of microalgal bioremediation of greenhouse effluents in the Nordic countries.